Analyzing the Performance of Searchable Symmetric Encryption over Huawei Cloud - Silveira, Matheus M.; Silva, Danielle S.; Oliveira, Luiz Z.; Gomes, Rafael L. (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2023: Anais Estendidos do XLI Simpósio Brasileiro de Redes de Computadores e Sistemas DistribuídosDO - 10.5753/sbrc_estendido.2023.465, 2023)
Cloud computing environments store data from companies and end users, bringing reliability and scalability to this remote access. Additionally, encryption techniques have been applied to protect this data in the cloud, where Searchable Symmetric Encryption (SSE) enables a fast search of keywords in encrypted databases. However, the configuration of the cloud environment directly impacts the processing time of SSE and, consequently, affects Service Level Agreement (SLA) requirements. Within this context, this paper analyzes the impact of Huawei Cloud configuration over the SSE task, encompassing the possible existing options regarding computing and architectures available. The experiments performed using a real database over the Huawei Cloud suggest the most suitable configuration according to the requirements needed to meet.